2003
DOI: 10.1007/s10329-002-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of urinary reproductive hormones in great apes

Abstract: Urinary estrone conjugates (E 1 C), pregnanediol-3-glucuronide (PdG), and follicle-stimulating hormone (FSH) were determined by enzyme immunoassays (EIAs) during the normal menstrual cycle in the orangutan, gorilla, chimpanzee, and bonobo. Furthermore, the data were compared to those levels in the human and long-tailed macaque. The results showed a typical preovulatory E 1 C surge and postovulatory increase in PdG in all species. The pattern of E 1 C during the menstrual cycle in the great apes more closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…18 In many species, estrone-3-glucuronide (E 1 G) and pregnanediol-3-glucuronide (PdG) are abundant metabolites of estrogen and progesterone excreted into urine, which accurately reflect changes in circulating hormones and the maintenance of pregnancy, respectively. [19][20][21] Therefore, it is important to measure the concentrations of these hormone metabolites in urine to assess the endocrinological changes during pregnancy. In this study, urinary PLAP, E 1 G, and PdG concentrations were compared among four female Bornean orangutans who gave either a stillbirth or live birth.…”
Section: Introductionmentioning
confidence: 99%
“…18 In many species, estrone-3-glucuronide (E 1 G) and pregnanediol-3-glucuronide (PdG) are abundant metabolites of estrogen and progesterone excreted into urine, which accurately reflect changes in circulating hormones and the maintenance of pregnancy, respectively. [19][20][21] Therefore, it is important to measure the concentrations of these hormone metabolites in urine to assess the endocrinological changes during pregnancy. In this study, urinary PLAP, E 1 G, and PdG concentrations were compared among four female Bornean orangutans who gave either a stillbirth or live birth.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and some hominids, including gorilla, chimpanzee, bonobo, and orangutan, it was reported that urinary estrone conjugate (E 1 C) was elevated during the follicular phase, and urinary pregnanediol-3glucuronide was elevated during the luteal phase, while in the female long-tailed macaque (Macaca fascicularis) urinary E 1 C did not increase during the luteal phase [7,16,26]. In our study, the female did not show an obvious elevation of urinary E during the luteal phase.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 2g of all samples were then stored in 50 mL plastic tubes, with 35 mL of silica gel added to allow a complete desiccation of the pellet. Fecal samples were then analyzed for estrone conjugates (E1C) and pregnanediol-3-glucuronide (PdG) using previously described and validated enzyme immunoassays (EIA) (for further details see [ 42 , 51 ]), with a few modifications. Dry feces (0.25 g) were shaken with 2.5 mL of modified phosphate buffer (0.1 M, pH 7.0, 0.1% BSA with 0.05% tween-20) at room temperature for 24 hr, and then centrifuged (3,000 rpm, 10 min).…”
Section: Methodsmentioning
confidence: 99%